2020
DOI: 10.1007/s42452-020-03616-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of zein nanofibers for the controlled delivery of essential amino acids for fish nutrition

Abstract: In the present paper, films and nanofibers of zein and zein/tryptophan were produced by casting and eletrospinning. The films and nanofibers were characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and controlled release and digestibility tests. In vitro releasing of tryptophan was evaluated using a spectrophotometer UV-Vis. Interactions between tryptophan and zein were confirmed by thermal (TGA) and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…TGA (Figure S3) was employed to examine the material composition in relation to the proportion of each constituent. Pure zein exhibited two weight losses, where the first occurred below 100 °C and was attributed to the removal of physically adsorbed water. , The second loss is associated with the decomposition of the main protein structure of zein, resulting from the breakage of low-energy intermolecular bonds. , The overall residue accounted for 14% of the total. The MnO 2 NSs displayed two distinct stages of mass loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGA (Figure S3) was employed to examine the material composition in relation to the proportion of each constituent. Pure zein exhibited two weight losses, where the first occurred below 100 °C and was attributed to the removal of physically adsorbed water. , The second loss is associated with the decomposition of the main protein structure of zein, resulting from the breakage of low-energy intermolecular bonds. , The overall residue accounted for 14% of the total. The MnO 2 NSs displayed two distinct stages of mass loss.…”
Section: Resultsmentioning
confidence: 99%
“…Pure zein exhibited two weight losses, where the first occurred below 100 °C and was attributed to the removal of physically adsorbed water. 44,45 The second loss is associated with the decomposition of the main protein structure of zein, resulting from the breakage of low-energy intermolecular bonds. 44,45 The overall residue accounted for 14% of the total.…”
Section: Morphological and Thermal Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, zein has shown low digestibility and controlled release capability [43,44]; thus, its nanofibers have drawn great interest in the controlled delivery of bioactive compounds. Silva et al (2020) indicated a lower release rate of tryptophan from zein nanofibers compared with that from zein films [45]. In the study by Defrates et al (2021), a more sustained release of model drugs (rifampin, rhodamine B, and crystal violet) was observed in zein fibers compared with zein films [46].…”
Section: Introductionmentioning
confidence: 96%